(untitled) (Scientific journal of the Fergana State University, 2024)
The article reveals the essence of independent work of students on a foreign language as an integral part of the process of mastering the foreign language teaching program at the Higher Education Institution. It covers all aspects of foreign language learning of students’ independent work and largely determines the results and quality of mastering the subject of "Foreign Language". In this regard, the planning, organization, implementation and control of students’ independent work in a foreign language is of a particular importance and requires methodological guidance and methodological support.